21. -Amylase and -Glucosidase Inhibitors from Plant Extracts - Daud AK, M; Juliani, Juliani; Sugito, Sugito; Abrar, Mahdi (Jurnal Medika Veterinaria, 2019)
About 80% of diabetic people have come from developing countries. Indonesia is seventh of diabetics. Diabetes is a disease as a result of metabolic disorder that caused by lack of insulin secretion and/or insulin do not work properly, so that the sugar highly accumulated in blood (characterized by hyperglycemia). Normally, range of blood sugar is 70 - 110 mg / dL before meals and less than 140 mg / dL after meals. One therapeutic approach to control blood sugar level is to inhibit the activity of starch hydrolysis enzymes, namely -amylase and -glucosidase. The active compounds of plant extracts have a unique and diverse structure compared to synthetic ones. This characteristics are important because the inhibition of enzyme activity by active compounds from plant extracts is known to make the formation of chemical bonds (affinity) between the active compounds and enzymes. A number of active compounds from plant extracts such as tannins, flavonoids, polysaccharides, saponins, terpenoids are known to inhibit the activity of -amylase and -glucosidase. In this study, we discuss some active compounds that inhibit -amylase and -glucosidase enzyme from plant extracts.